Pengembangan Ekonomi Pondok Pesantren Melalui Pemberdayaan Masyarakat Pesisir - Achmad Febrianto; Saifuddin Saifuddin (Universitas Muhammadiyah Prof. DR. HAMKA, 2021)
This study discusses the economic development of Islamic boarding schools in Probolinggo Regency through empowering coastal Muslim communities by producing marine processed products, where the boarding school has provided a new nuance for coastal communities in the form of economic improvement. Researchers used a phenomenological qualitative method. The purpose of this study is to determine the strategies and methods of the religious boarding school approach in improving the economy of the coastal Muslim community. The results of the study (1) In the efforts made by the Nurul Jadid Islamic boarding school in formulating the formulation of coastal community empowerment patterns must be based on two approaches, the first is the approach. in increasing the capacity of the community independently and creating opportunities for economic development for the community, (2) in developing the economy of the community along the Pondok Pesantren Nurul Jadid explained some of the efforts made such as seeing the social structure, economic equality, education on the values ​​of economic independence, community participation, and community involvement in regional development.